Cumulative social risk exposure and risk of cancer mortality in adulthood. Issue 1 (December 2015) - Caleyachetty, Rishi; Tehranifar, Parisa; Genkinger, Jeanine; Echouffo-Tcheugui, Justin; Muennig, Peter
Abstract Background Adults in the United States (U.S) can be simultaneously exposed to more than one social risk factor over their lifetime. However, cancer epidemiology tends to focus on single social risk factors at a time. We examined the prospective association between cumulative social risk exposure and deaths from cancer in a nationally representative sample of U.S. adults. Methods The study included 8745 adults (aged ≥ 40 years) in the NHANES Survey III Mortality Study over a median follow-up of 13.5 years (1988-1994 enrollment dates and 1988 through 2006 for mortality data). Social risk factors (low family income, low education level, minority race, and single-living status) were summed to create a cumulative social risk score (0 to ≥3). We used Cox proportional hazard models to estimate age- and sex-adjusted hazard ratios (HRs) and 95 % confidence intervals (95 % CI) for the association between cumulative social risk with deaths from all-cancers combined, tobacco-related cancers, and screening-detectable cancers. Results Deaths from all-cancers combined (P for trend = 0.001), tobacco-related cancers (P for trend = <0.001), and lung cancer (P for trend = 0.01) increased with an increasing number of social risk factors. As compared with adults with no social risk factors, those exposed to ≥3 social risk factors were at increased risk of deaths from all-cancers combined (HR = 1.8, 95 % CI = 1.3-2.4), tobacco-related cancers (HR = 2.6, 95 % CI: 1.6-4.0), and lung cancer (HR = 2.3, 95 % CI = 1.3-4.1). Conclusions U.S. adults confronted by higher amounts of cumulative social risk appear to have increased mortality from all-cancers combined, tobacco-related cancers, and lung cancer. An enhanced understanding of the cumulative effect of social risk factors may be important for targeting interventions to address social disparities in cancer mortality.